Tumor-infiltrating lymphocytes and response to neoadjuvant chemotherapy with or without carboplatin in human epidermal growth factor receptor 2-positive and triple-negative primary breast cancers - Denkert, Carsten; Minckwitz, Gunter von; Brase, Jan Christoph; Sinn, Bruno V.; Gade, Stephan; Kronenwett, Ralf; Pfitzner, Berit M.; Salat, Christoph; Loi, Sherene; Schmitt, Wolfgang D.; Schem, Christian; Fisch, Karin; et al. (Journal of clinical oncology, 2015)
Modulation of immunologic interactions in cancer tissue is a promising therapeutic strategy. To investigate the immunogenicity of human epidermal growth factor receptor 2 (HER2) -positive and triple-negative (TN) breast cancers (BCs), we evaluated tumor-infiltrating lymphocytes (TILs) and immunologically relevant genes in the neoadjuvant GeparSixto trial.
Published online ahead of print on December 22, 2014
Das PDF enthält zusätzlich einen Anhang von 8 Seiten
Gesehen am 13.10.2020